IMPLEMENTATION OF GOVERNMENT REGULATION NUMBER 39 OF 2023 FOR THE DEVELOPMENT OF REGIONAL WATER SUPPLY SYSTEMS (SPAM) KARIAN NON KPBU BANTEN PROVINCE - Sriharyati, Santy; Mulyasana, Dedi; Wahjudin, Lisdawati (SULTANIST: Jurnal Manajemen dan Keuangan, 2025)
Land acquisition for infrastructure development is a strategic step that must be taken by the government to fulfill the basic needs of society. This paper examines the dynamics of land acquisition implementation by focusing on the procedures and policies stipulated in Government Regulation (PP) No. 19 of 2021 concerning the Implementation of Land Acquisition for the Public Interest. Along with the issuance of PP No. 39 of 2023, it is necessary to adjust the existing policies so that they remain relevant and effective. This study applies a descriptive qualitative approach in exploring the crucial stages of the land acquisition process, which includes the planning phase, the preparation stage, the implementation of activities, and the final handover process. In addition, the study also explores the application of the policy in the context of infrastructure projects, particularly in terms of managing the public interest, handling operational obstacles, This study uses a qualitative descriptive approach to analyze the stages of land acquisition, from planning to handover. The study results show that proper implementation of land acquisition policies can accelerate the infrastructure development process. Therefore, a review of the Land Acqusition Planning Document Dokumen Perencanaan Pengadaan Tanah/ DPPT) is needed as mandated by Government Regulation No. 39 of 2023. In addition, solid inter-agency coordination and in-depth understanding of applicable regulations are key to successful implementation. The recommendations from this study are expected to strengthen the government's role in the provision of land for the public interest and support sustainable development for the welfare of the community.